2018
DOI: 10.17219/acem/74178
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine level in patients with obstructive sleep apnea/hypopnea syndrome and the impact of continuous positive airway pressure treatment

Abstract: The change of the Hcy level was not proportional to the severity of the disease in different groups of OSAHS patients, and CPAP did not affect the Hcy levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…In two studies, patients with mild disease displayed significantly higher MDA values when compared to those with severe form (mean difference range, −0.04 to −0.55) [39,49]. By contrast, in the remaining seven studies, the MDA value was found to be higher in patients with severe disease (mean difference range 0.63 to 1.65), with a significant difference in four studies [35,37,42,52]. The pooled results showed that MDA concentrations were significantly higher in patients with severe disease (SMD 0.59; 95% CI 0.05 to 1.12, p = 0.03; I 2 = 86.7%, p < 0.001) when compared with mild disease.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…In two studies, patients with mild disease displayed significantly higher MDA values when compared to those with severe form (mean difference range, −0.04 to −0.55) [39,49]. By contrast, in the remaining seven studies, the MDA value was found to be higher in patients with severe disease (mean difference range 0.63 to 1.65), with a significant difference in four studies [35,37,42,52]. The pooled results showed that MDA concentrations were significantly higher in patients with severe disease (SMD 0.59; 95% CI 0.05 to 1.12, p = 0.03; I 2 = 86.7%, p < 0.001) when compared with mild disease.…”
Section: Resultsmentioning
confidence: 86%
“…Conversely, age (t = −2.06, p = 0.049), assay type (t = 2.31, p = 0.03) and publication year (t = 2.08, p = 0.048) were significantly associated with the SMD. In order to evaluate the relationship between effect size and disease severity we performed a meta-analysis in a sub-group of nine studies reporting MDA concentrations in groups with different disease severity [32,35,37,38,42,45,47,49,52]. The forest plot for MDA concentrations in mild and severe OSA patients is reported in Figure 8.…”
Section: Resultsmentioning
confidence: 99%
“…Though the homocysteine changes varied from study to study, substantial decreases were observed in most of them, which were recognized to be related to the improvements in sleep and desaturation-related indices. 18,32 This longitudinal cohort study aimed to evaluate the alterations of homocysteine levels in the severe OSA patients who received TORS-assisted upper airway surgery, and discovered the associations with the improvements in PSG parameters. We found that not only the majority of patients' PSG data improved generally, but the homocysteine level significantly decreased from 12.1 ± 3.9 to 11.4 ± 3.7 mcmol/L (difference = −0.7 ± 2.8 mcmol/L, p = .001) postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are studies observing the changes in plasma homocysteine levels following CPAP or mandibular advancement device (MAD) therapy. [18][19][20][21] However, none of the studies discussed the alteration of homocysteine level in OSA patients treated with upper airway surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation